2020
DOI: 10.14744/anatoljcardiol.2020.94884
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and in-hospital outcomes of acute decompensated heart failure patients with and without atrial fibrillation

Abstract: Clinical characteristics and in-hospital outcomes of acute decompensated heart failure patients with and without atrial fibrillation Introduction Atrial fibrillation (AF) is the most common chronic cardiac arrhythmia and heart failure (HF) is an important cause of cardio-vascular mortality (1, 2). The prevalence of AF and HF increases with age and often coexist (3). The coexistence of AF and HF is associated with an increased rehospitalization, morbidity, and mortality risk (4). AF directly causes the worsenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
(67 reference statements)
1
7
0
Order By: Relevance
“…Therefore, this study sought to determine the frequency of AF among patients with ADHF in Pakistan. Our results indicate that the prevalence of AF among patients with ADHF was 38.1%, which is supported by data from Turkey, where 39% of patients with ADHF had a history of AF [ 5 ]. However, 25.4% of the subjects had AF in Cameroon [ 6 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, this study sought to determine the frequency of AF among patients with ADHF in Pakistan. Our results indicate that the prevalence of AF among patients with ADHF was 38.1%, which is supported by data from Turkey, where 39% of patients with ADHF had a history of AF [ 5 ]. However, 25.4% of the subjects had AF in Cameroon [ 6 ].…”
Section: Discussionsupporting
confidence: 87%
“…Mortality was high for patients hospitalized more than once for AF and ADHF [ 13 ]. According to the literature, 39% of patients with ADHF have a positive history of AF and were often in advanced age [ 1 , 2 , 5 ]. AF in ADHF was associated with stroke, increased blood pressure, and valvular diseases [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step is to use the ultrasound probe to scan different positions; the second step is to select the standard section; the third step is to measure and diagnose the determined standard section. After using it, it is found that it has certain limitations, which will be targeted at the section of a specific moment in the cardiac cycle, resulting in poor performance of the final model [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Of note, one of the most common entities in CVDs mainly observed among the elderly population is heart failure (HF). 2 …”
Section: Introductionmentioning
confidence: 99%